Avaliando a Capacidade de uma Rede de Terceira Geração UMTS/WCDMA quando Submetida a Tráfego Multimídia - Jucá, Paulyne (2007)
This paper presents a study on the behavior of the UMTS third generation cellular system using the WCDMA interface with multimedia applications. A simulator was developed and its main characteristics are described. Based on the simulator, an evaluation of the capacity of a one-cell UMTS network with multimedia traffic was performed, involving variable number of users, types of network traffic (voice, video and Web) and different speeds